SIGNIFICANCE OF SYSTEMATIC CONTROL OF HIGHLY DANGEROUS PATHOGENS CIRCULATING IN POPULATIONS OF WILD MIGRATORY ANIMALS - M. V. Zhiltsova; V. M. Zakharov; V. P. Semakina (Ветеринария сегодня)
The paper presents analysis of published data and results of epizootic examination of FMD-infected regions associated with migration of FMD-susceptible wild ruminants. Their role in disease spread has been demonstrated. The necessity to carry out regular epizootic monitoring of wild animal populations for FMD and other highly dangerous diseases has been justified.